Optimization Model of Fishery Products Supply Chain Using Mixed Integer Linear Programming Method - Nurdin Nurdin; Taufiq Taufiq; Bustami Bustami; Marleni Marleni; Khairuni Khairuni (Universitas Medan Area, 2023)
North Aceh is one of the districts in Aceh province that has great potential in the marine and fisheries sector. Many capture fisheries resources have become superior commodities, because some parts of North Aceh are suppliers of capture fisheries products. As for the problem in this study, there are several sub-districts in North Aceh district experiencing a shortage of fishery products supply due to their location far from the coastline, causing high logistics costs for the supply chain of fishery products. Therefore, an optimization model for planning the supply chain of fishery products is needed. The purpose of this study is to create a supply chain optimization model for capture fisheries using the mixed integer linear programming method. The steps involved in this research are compiling research instruments and literature review, collecting and analyzing data, determining parameters and decision variables, formulating objective functions and model constraint functions, designing optimization models, testing and modeling simulations. This model can minimize the operational costs of the fishery product supply chain from suppliers to consumers. Testing and simulating this model using the lindo program, with the result that the maximum value of the objective function is 36 in the 15th iteration.